Influence of different plant growth regulators and zinc levels on growth and quality aspects of fenugreek (Trigonella foenum-graecum L.) under semi-arid conditions - A K Mahawar, T V Yadav, A Singh, S P Singh, (Journal of Spices and Aromatic Crops, 2015)
The experiment was conducted to study the influence of different plant growth regulators and zinc (Zn) levels on growth and quality attributes of fenugreek (Trigonella foenum-graecum L.). The results revealed that foliar application of triacontanol and NAA increased the growth attributes and uptake of N, P and Zn significantly over control and thiourea application. Growth regulator sprays were superior to control with regard to N, P and Zn concentration in seed & straw and protein content in seed. Application of Zn @ 4 kg ha-1 significantly increased the growth and quality attributes compared to 0 and 2 kg Zn ha-1.